Expert Consensus on Diagnosis and Molecular Testing Strategies for Non-Small-Cell Lung Cancer in India - Bivas Biswas; Trupti Pai; Nirmal Raut; Vidya Manur Narasimhamurthy; Bijal Kulkarni; Ashish Singh; Sunil Pasricha; Jayesh Deshmukh; Sewanti Limaye (Indian Journal of Medical and Paediatric Oncology)
This review aims to establish expert consensus on biomarker testing for non-small-cell lung cancer (NSCLC) in India, evaluating diagnostic practices, adherence to international guidelines, and test utility and comparing clinically validated assays with laboratory-developed tests. In round 1, experts voted on 41 statements covering various aspects of NSCLC diagnostics. Responses were graded using a 5-point Likert scale, categorizing agreement levels as high, moderate, or low based on expert consensus percentages. After thorough deliberations during round 2, consensus was reached on 32 statements underscoring the necessity for early diagnosis of NSCLC. Key issues include misdiagnosis with tuberculosis and low or delayed specialist referral rates. Although formal programs are limited by awareness, resources, and data gaps; low-dose computed tomography (LDCT) screening in community settings is advocated. Consensus was reached among experts that most lung cancers are diagnosed at advanced stages in India. The delay in diagnosis was mainly due to misdiagnosis with tuberculosis and delayed referrals to specialists for evaluation. The consensus acknowledged the need to enhance lung cancer awareness and utilization of LDCT in high-risk individuals as a screening methodology in the community.